2023
DOI: 10.3390/microorganisms11051246
|View full text |Cite
|
Sign up to set email alerts
|

Characteristic Gut Bacteria in High Barley Consuming Japanese Individuals without Hypertension

Abstract: Background: Barley, a grain rich in soluble dietary fiber β-glucan, is expected to lower blood pressure. Conversely, individual differences in its effects on the host might be an issue, and gut bacterial composition may be a determinant. Methods: Using data from a cross-sectional study, we examined whether the gut bacterial composition could explain the classification of a population with hypertension risks despite their high barley consumption. Participants with high barley intake and no occurrence of hyperte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 60 publications
0
9
0
Order By: Relevance
“…Elevated levels of TMAO can inhibit reverse cholesterol transport and bile acid metabolism, amplifying vascular inflammation and cellular apoptosis, leading to atherosclerosis ( Chen et al, 2023 ). Moreover, other studies have shown the links of Lachnoclostridium with conditions like obesity ( Guo et al, 2023 ), hypertension ( Maruyama et al, 2023 ), and diabetes ( Zang et al, 2023 ). Our findings, suggesting an association between Lachnoclostridium and PAD, further underscore the role of this bacterial genus in vascular diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated levels of TMAO can inhibit reverse cholesterol transport and bile acid metabolism, amplifying vascular inflammation and cellular apoptosis, leading to atherosclerosis ( Chen et al, 2023 ). Moreover, other studies have shown the links of Lachnoclostridium with conditions like obesity ( Guo et al, 2023 ), hypertension ( Maruyama et al, 2023 ), and diabetes ( Zang et al, 2023 ). Our findings, suggesting an association between Lachnoclostridium and PAD, further underscore the role of this bacterial genus in vascular diseases.…”
Section: Discussionmentioning
confidence: 99%
“…These variations can influence individual responses, categorizing some as “responders” who exhibit the anticipated effects, while others as “non-responders.” For instance, in a study involving mice fed barley, an elevation in Prevotella was detected among responders, where improved glucose tolerance was noted. This change was attributed to the production of succinic acid by Prevotella , resulting from the decomposition of β-glucan present in barley, which subsequently modulated glucose metabolism in the liver ( 38 ). To further elucidate the characteristics of the intestinal environment in subjects with heightened IgA and to discern potential similarities or differences between the CF and FG cohorts, we undertook a correlation analysis linking fecal IgA levels with the intestinal milieu.…”
Section: Discussionmentioning
confidence: 99%
“…Principal component analysis (PCA) and multidimensional scaling (MDS or principal coordinates analysis/PCoA) are often used for gut microbiome analyses [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. PCA and PCoA are types of unsupervised machine learning.…”
Section: Introductionmentioning
confidence: 99%
“…Gut microbiome analysis is a field of information engineering. Moreover, in recent years, bacteriological studies have sometimes been conducted using the results from the gut microbiome analysis [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. However, misinformation is pervasive in the human microbiome literature [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation